Answer:
transformation
Step-by-step explanation:
this is when one form of energy forms into another form, and it can be transferred into a new object or location
Answer:
40
Step-by-step explanation:
3a + 2b =
3(10) + 2(5)
30 + 10 = 40
I hope this helps!
Have a great day!
Answer:
a = 3
Step-by-step explanation:
Factor both expressions
x² - x - 6
Consider the factors of the constant term (- 6) which sum to give the coefficient of the x- term (- 1)
The factors are - 3 and + 2 , since
- 3 × 2 = - 6 and - 3 + 2 = - 1 , thus
x² - x - 6 = (x - 3)(x + 2)
-----------------------------------
x² + 3x - 18
consider factors of constant term (- 18) which sum to give the coefficient of the x- term (+ 3)
The factors are + 6 and - 3 , since
6 × - 3 = - 18 and 6 - 3 = + 3 , thus
x² + 3x - 18 = (x + 6)(x - 3)
Both expressions have a common factor of (x - 3)
Compare with (x - a ), then a = 3
Answer: I think that the cost now from hotel 5 would be $15.00.
Step-by-step explanation:
5 hours = $5.00
10 hours = $10.00
15 hours = $15.00
20 hours = $20.00
25 hours = $25.00
Answer: Make an equation explaining how blue fire hydrant "b" relates to green fire hydrant "g". Once you have your equation choose the one on the multiple choice that matches your work.
Step-by-step explanation: